HPV in HIV-Infected Women: Implications for Primary Prevention - McKenzie, Nathalie Dauphin; Kobetz, Erin N.; Ganjei-Azar, Parvin; Rosa-Cunha, Isabella; Potter, JoNell E.; Morishita, Atsushi; Lucci, Joseph A.; Guettouche, Toumy; Hnatyszyn, James H.; Koru-Sengul, Tulay (Frontiers in Oncology, 2014)
Background: There is growing evidence that HIV-infected women might have a different HPV type distribution in cervical dysplasia specimens as compared to the general population. This has implications for primary prevention. Objective: We aimed to obtain preliminary data on the human papillomavirus (HPV) genotypes prevalent in histological samples of HIV-infected women with CIN 3/ CIS of the cervix in Miami, Florida. Method: Retrospective data were collected on HIV-infected women referred to the UM-JMH colposcopy clinic between years 2000 and 2008. The histology slides of CIN3/CIS biopsies underwent pathological review and sections were cut from these archived specimens for HPV DNA extraction. HPV genotyping was then performed using the GeneSquare™ HPV genotyping assay. We report on our first set of 23 samples. Results: Eight high risk HPV (HR-HPV) types were detected. Types in decreasing order of frequency were 16, 35, 45, 52, 59, 31, 58, and 56. Most cases had multiple infections. HPV type 16 was the most common (45%) followed by HPV-35 and -45 with equal frequency (40%). No samples contained HPV-18 Conclusion: Our preliminary data suggest that cervical dysplasia specimens of HIV-infected women more likely (55%) contain non -16 and -18 high risk HPV types. We show that this held true for histologically confirmed carcinoma in situ. Epidemiological studies guide vaccine development, therefore HPV type prevalence in CIS and invasive cervical cancer among HIV-infected women should be more rigorously explored to ensure that this highly vulnerable population receives appropriate primary prevention.